From Tafaqquh Fiddin to Applied Sciences: The Transformation of Islamic Education in Indonesia - Abdullah Hanif; Ilzamudin Ma'mur; Agus Gunawan (UIN Sunan Gunung Djati Bandung, 2024)
In facing the demands of globalisation and the Fourth Industrial Revolution, Islamic education in Indonesia encounters challenges to remain relevant by preserving religious values while responding to the need for practical skills. This study aims to explore the transformation of Islamic education in Indonesia, particularly in the context of the shift from the scholarly tradition of tafaqquh fiddin (deep understanding of religion) to applied sciences. The research evaluates how Islamic boarding schools (pesantren), Islamic schools (madrasah), and Islamic higher education institutions (PTKI, or Perguruan Tinggi Keagamaan Islam) adapt to the demands of globalisation and modern economic developments requiring practical and professional skills. This study employs a qualitative approach by analysing literature, curricula, and policies related to Islamic education in Indonesia. Data were collected from various sources such as journals, books, and policy documents. The findings reveal that Islamic education in Indonesia has undergone significant transformation. Pesantren have begun integrating vocational skills such as agribusiness and information technology, madrasah have broadened their focus to include academic education and practical skills, while PTKI have adopted non-religious programmes such as economics and health sciences. This transformation has produced graduates who not only possess profound religious understanding but also practical skills relevant to the modern job market. The study underscores the importance of integrating religious education with applied sciences to ensure the relevance of Islamic education in the modern era. These findings provide a foundation for the development of adaptive educational policies, such as competency-based curricula and support for vocational education. This research also offers a unique contribution to the literature on Islamic education by highlighting a significant shift in the scholarly tradition in Indonesia, particularly in balancing religious values with applicative skills for success in the professional world.